Resonance energy flow dynamics of coherently delocalized excitons in biological and macromolecular systems: Recent theoretical advances and open issues. (8th August 2012) - Jang, Seogjoo; Cheng, Yuan‐Chung
Abstract Recent experimental and theoretical studies suggest that biological photosynthetic complexes utilize the quantum coherence in a positive manner for efficient and robust flow of electronic excitation energy. Clear and quantitative understanding of such suggestion is important for identifying the design principles behind efficient flow of excitons coherently delocalized over multiple chromophores in condensed environments. Adaptation of such principles for synthetic macromolecular systems has also significant implication for the development of novel photovoltaic systems. Advanced theories of resonance energy transfer are presented, which can address these issues. Applications to photosynthetic light harvesting complex systems and organic materials demonstrate the capabilities of new theoretical approaches and future challenges.